The Icelandic media coverage of the constitutional assembly election - Kolbeins, Guðbjörg Hildur (Stjórnmál og stjórnsýsla, 2025)
On November 27, 2010, the people of Iceland elected 25 individuals to the country’s constitutional assembly. As there were 522 candidates for the 25 seats in the assembly, the media were faced with a new dilemma, i.e. how to ensure impartiality and objectivity in their coverage of the candidates and the subject matter. The present study compares the media coverage of the constitutional assembly election to two other national elections; the general election in the spring of 2009 and the municipal election in the spring of 2010. All news stories in the 13 major print, broadcast and online news outlets in Iceland were coded two weeks prior to each election. The results indicate that the national media almost ignored the constitutional assembly election in comparison to the other elections. There were 632 news stories on the general election, 590 stories on the municipal election but only 165 stories on the constitutional assembly election. The lack of coverage of the candidates for the constitutional assembly seems to reveal that the traditional media, i.e. the print and broadcast media, and the online media did not know how to best serve and inform the public in the democratic process.